Wątki dotyczące przemysłu na łamach „Ziemianina” i „Głosu Ziemiańskiego” 1917–1920 - Przeniosło, Marek (Studia z Historii Społeczno-Gospodarczej XIX i XX Wieku, 2010)
“Ziemianin” and “Głos Ziemiański” were the periodicals for the landowners. The first of them was published in the years 1917–1919 and was a monthly, the second appeared in 1920, three times a month. Both magazines had the same editor – Józef Janota Bzowski. The editorial staff of the periodicals realized that the landowners are mainly interested in the problems which are directly connected with agriculture. However, they also inserted other information, among them the questions concerning industry. Some branch of industry were preferable to other. Undoubtedly, the branch which are directly connected with agriculture: sugar industry, production of artificial fertilizers and production of farm machinery were preferable. However, the periodicals also published the papers concerning other branch of industry, even heavy industry. A certain number of articles referred to questions connected with electrification and necessity of developing of communication, especially a railway. Some papers concerning industry which inserted in both magazines were articles from other periodicals. Most often the articles coming from “Gazeta Rolnicza” were used.